30-day morbidity and mortality of sleeve gastrectomy, Roux-en-Y gastric bypass and one anastomosis gastric bypass: a propensity score-matched analysis of the GENEVA data - Singhal, Rishi; Cardoso, Victor Roth; Wiggins, Tom; Super, Jonathan; Ludwig, Christian; Gkoutos, Georgios V.; Saydam, Mehmet (Springer Nature, 2022)
Background: There is a paucity of data comparing 30-day morbidity and mortality of sleeve gastrectomy (SG), Roux-en-Y gastric bypass (RYGB), and one anastomosis gastric bypass (OAGB). This study aimed to compare the 30-day safety of SG, RYGB, and OAGB in propensity score-matched cohorts. Materials and methods: This analysis utilised data collected from the GENEVA study which was a multicentre observational cohort study of bariatric and metabolic surgery (BMS) in 185 centres across 42 countries between 01/05/2022 and 31/10/2020 during the Coronavirus Disease-2019 (COVID-19) pandemic. 30-day complications were categorised according to the Clavien–Dindo classification. Patients receiving SG, RYGB, or OAGB were propensity-matched according to baseline characteristics and 30-day complications were compared between groups. Results: In total, 6770 patients (SG 3983; OAGB 702; RYGB 2085) were included in this analysis. Prior to matching, RYGB was associated with highest 30-day complication rate (SG 5.8%; OAGB 7.5%; RYGB 8.0% (p = 0.006)). On multivariate regression modelling, Insulin-dependent type 2 diabetes mellitus and hypercholesterolaemia were associated with increased 30-day complications. Being a non-smoker was associated with reduced complication rates. When compared to SG as a reference category, RYGB, but not OAGB, was associated with an increased rate of 30-day complications. A total of 702 pairs of SG and OAGB were propensity score-matched. The complication rate in the SG group was 7.3% (n = 51) as compared to 7.5% (n = 53) in the OAGB group (p = 0.68). Similarly, 2085 pairs of SG and RYGB were propensity score-matched. The complication rate in the SG group was 6.1% (n = 127) as compared to 7.9% (n = 166) in the RYGB group (p = 0.09). And, 702 pairs of OAGB and RYGB were matched. The complication rate in both groups was the same at 7.5 % (n = 53; p = 0.07). Conclusions: This global study found no significant difference in the 30-day morbidity and mortality of SG, RYGB, and OAGB in propensity score-matched cohorts. © 2021, The Author(s).
Keywords: COVID-19; Diabetes Mellitus, Type 2; Gastrectomy; Gastric Bypass; Humans; Morbidity; Obesity, Morbid; Propensity Score; Retrospective Studies; Treatment Outcome; antidiabetic agent; adult; Article; bariatric surgery; body mass; cohort analysis; controlled study; coronavirus disease 2019; demographics; female; gastric bypass surgery; human; hypercholesterolemia; hypertension; insulin dependent diabetes mellitus; major clinical study; male; morbidity; multicenter study; non insulin dependent diabetes mellitus; non-smoker; observational study; one anastomosis gastric bypass; pandemic; postoperative complication; Roux-en-Y gastric bypass; sleep disordered breathing; sleeve gastrectomy; surgical mortality; adverse event; complication; gastrectomy; morbid obesity; morbidity; non insulin dependent diabetes mellitus; propensity score; retrospective study; treatment outcome